Clinical Profile of Dengue Fever Outbreak in 2017- A Cross-Sectional Study from South Kerala - Vincy Nelson; Teju P Thomas; Sabu Stephen; Sony Simon (Medsci Publications, 2020)
Introduction: Dengue epidemics are a serious public health problem across the world. The recent outbreak of dengue in Kerala has shown different clinical patterns and high morbidity. This study focuses on the clinical features, laboratory investigations and outcome of dengue patients admitted in a tertiary care centre of south Kerala. Materials & Methods: It was a cross sectional study done on the dengue cases done on 190 cases which were admitted in our hospital during the outbreak (July to august 2017). Results: Out of the 190 patients, majority of the population were males 105(55.3%) compared to females 85(44.7%). 172(90.5%) were positive for NS1 antigen card test during admission. IgM assay was positive for 129(67.9%), 47 (24.7%) cases were referred from outside. Majority had platelet count of one lakh to 500000 62(32.6%) during admission. 116(61.1%) had altered liver function and 26(13.7%) had altered renal function. 32(16.8%) received platelet transfusion. There was a mortality rate of 14 (7.3%). There were 2 deaths reported due to subdural hematoma which was unlikely with dengue. Conclusion: Dengue infection is increasing due to rapid urbanization and unplanned townships followed by waste disposal. Fever associated with headache, retro orbital pain, erythematous rash, conjunctival congestion and itching in palms and soles along with thrombocytopenia, Leucopenia, elevated liver transaminases should prompt a clinician on the possibility of dengue infection. Early diagnosis and prompt management can save many lives during an outbreak.